2020
DOI: 10.3955/046.093.0307
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity and Host-Specificity of Frankia Bacteria Associated with Sympatric Populations of Alnus rubra and Alnus rhombifolia in Oregon

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…and their mycorrhizal fungi (Molina, 1981), our finding that cultivable fungal endophyte communities also differ between host species is not surprising. Although we did not focus on Frankia in this study, the fact that bacterial endophyte communities did not differ by host aligns with findings by Balkan et al (2020) that A. rubra and A. rhombifolia lack strong host specificity regarding their Frankia mutualists, implicating potential general cross‐compatibility of bacterial symbionts within Alnus .…”
Section: Discussionsupporting
confidence: 85%
“…and their mycorrhizal fungi (Molina, 1981), our finding that cultivable fungal endophyte communities also differ between host species is not surprising. Although we did not focus on Frankia in this study, the fact that bacterial endophyte communities did not differ by host aligns with findings by Balkan et al (2020) that A. rubra and A. rhombifolia lack strong host specificity regarding their Frankia mutualists, implicating potential general cross‐compatibility of bacterial symbionts within Alnus .…”
Section: Discussionsupporting
confidence: 85%
“…Currently, studies on actinorhizal symbiosis have mainly focused on the morphological structure of nodules, isolated cultures of Frankia , and the diversity of microbial communities in root nodules. Some studies have suggested that nodules of actinorhizal plants contain more than one species of Frankia , and that Frankia diversity in nodules may be related to host plant species, the geographical environment, and soil texture, but not to the abundance of Frankia in the soil ( Tekaya et al., 2018 ; Balkan et al., 2020 ). In addition, some non- Frankia microbes such as Streptomyces, Nocardia, and Micromonospora in nodules, may assist nodulation and promote plant growth ( Trujillo et al., 2015 ; Alekhya and Gopalakrishnan, 2017 ; Ghodhbane-Gtari et al., 2019 ; Karthikeyan et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…are important in the dynamic succession and nutrient cycle of many ecosystems ( Roy et al, 2007 ; Kennedy et al, 2010 ). At present, research on alder symbiotic N fixation focuses mostly on the diversity of and symbiotic relationship with nitrogen-fixing bacteria in root nodules ( Balkan et al, 2020 ; Wolfe et al, 2022 ; Vemulapally et al, 2022a ), while research on the actinobacteria and Frankia found in the root nodules of varied ploidy Alnus spp. has fallen behind in terms of community composition, structural diversity, and N fixation capacity.…”
Section: Introductionmentioning
confidence: 99%